Analysis of the Relationship Between Leadership Style and Employee Performance - Dolok, Andrew Hutur (Dinasti International Journal of Management Science, 2025)
Leadership patterns have a significant impact on employee performance within an organization. Effective leaders can motivate employees to achieve organizational goals in a more productive, creative, and innovative manner. This article uses a literature review approach to obtain relevant results. After examining various patterns and research findings from multiple sources, it is found that there is a strong relationship between leadership patterns and performance, which also influences the daily conditions of the organization as well as a positive work environment.